Hvalreki : My body is over the ocean - the sea. - Runólfsson, Halldór Björn; The Alma Löv Museum, Östra Amtervik (Sweden : The Alma Löv Museum, 2002)
Ásmundsson, Ásmundur ; Magnússon, Daniel ; Saebjörnsson, Egill ; Haraldsdóttir, Erla S. ; Thórarinsdóttir, Erla ; Fridriksdóttir, Gabriela ; Hjartardóttir, Gudrún Vera ; Hákon, Hulda ; Stefánsdóttir, Ilmur ; Óskar, Jón ; Blöndal, Margrét H. ; Björnsdóttir, Sara ; Eyfjörd, Steingrimur ; Björnsdóttir, Svava
The Alma Löv Museum, Östra Amtervik, 8. June - 22. August 2002 / 2002 Icelandproject
kunstcatalogus